The Effect of Consumption of Boiled Red Beans (Phaseolus Vulgaris L) on Hemoglobin Levels in Adolescent in Institute Of Health Science (STRADA) Indonesia - Wahyuni, Candra; Mufida, Riza Tsalatsatul; Astikasari, Nita Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Anemia in general is a condition where hemoglobin and erythrocyte levels are lower than normal Anemia that is occurred by many adolescents due to Fe deficiency and can be called Fe deficiency anemia (Tarwoto, 2014). The purpose of this study was to determine the effect of consumption of boiled red beans (Phaseolus Vulgaris L) on hemoglobin levels in adolescents in Institute of Health Science (STRADA), Kediri. The research design used was pre-experiment with one group pre-posttest design. The population in this study was all third semester students in Institute of Health Science (STRADA) who experienced anemia with a sample of 18 respondents. The sampling technique used was purposive sampling. The results showed that all (100%) had mild anemia before treatment, after the treatment, the results of all respondents (100%) experienced a change to non-anemia. Based on the statistical results using Wilcoxon test, the obtained p value = 0.005 <α 0.05, then H 0 is rejected and H1 accepted, which means there is an effect of boiled red beans (PhaseolusvulgarisL) on hemoglobin levels in adolescents in the Institute of Health Science (STRADA), Kediri. It can be concluded that boiled red beans (Phaseolus Vulgaris L) contain iron, which is useful for increasing hemoglobin levels in the blood. It is recommended for respondents to use boiled red beans as food to prevent anemia.